PEMBERDAYAAN PEKERJA MIGRAN INDONESIA DI MALAYSIA MELALUI PELATIHAN KEWIRAUSAHAAN BERBASIS KOMUNITAS - Nugroho, Mahendra Adhi; Siswanto, Siswanto; Saputri, Agatha; Nugraha, R. Andro Ziliyo (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Indonesian Migrant Workers (PMI) make a significant contribution to the national economy through the remittances they send, making their role highly strategic for national development. However, many PMIs still face limitations in personal financial management and lack entrepreneurial skills upon returning to Indonesia. In response to these challenges, this international community service program was designed to empower PMIs in Malaysia through community-based entrepreneurship training. The program was a collaboration between Universitas Negeri Yogyakarta, Sanggar Bimbingan Pantai Dalam Kuala Lumpur, and Sunway University. The training was conducted in three stages: two online sessions on June 29 and August 6, 2024, and one offline session on September 18, 2024, involving 30 participants. The materials covered financial literacy, digital marketing, strengthening of growth mindset, and entrepreneurial spirit development. The program evaluation showed a significant improvement in participants’ ability to manage personal finances, utilize digital media for business promotion, and develop an adaptive entrepreneurial mindset. This program is expected to serve as an effective model for PMI empowerment and be replicated in other destination countries.